Hybrid Management of Acute Portal Vein Thrombosis Complicated by Mesenteric Ischemia - Jinadasa, Sayuri P; Ghneim, Mira; Aicher, Brittany O; Kundi, Rishi; Karwowski, John; Diaz, Jose J; DuBose, Joseph J (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Acute portal vein thrombosis complicated by mesenteric ischemia requires emergent treatment to address the compromised bowel as well as the portal vein thrombus. We report a novel hybrid approach to managing this disease process. The procedure we discuss entails exploratory laparotomy and small bowel resection by the acute care emergency surgery team. Following this, the vascular surgery team performs a portal venogram through a branch mesenteric vein accessed through the laparotomy incision and then places a thrombolysis catheter. This technique and approach allows us to provide initial management efficiently and effectively under one operation.